Odpowiedzi

2009-10-02T12:53:46+02:00
Najlepsza Odpowiedź!
2009-10-02T14:07:44+02:00
A) 5!/4! +5! = ( 1*2*3*4*5)/(1*2*3*4) +1*2*3*4*5 =
5 + 120 = 125 , gdzie * - mnożenie

b) 5!+6!/6!-5! = , z poprzedniego 5 ! = 120 to 6 ! = 5!*6 = 120*6 =720
= 120 +720/720-120 = 840/620 = 42/31

c) (n+1)! - n!/(n-1)! =
[(n+1)!(n-1)! - n!]/(n-1)! = [ n!(n+1)(n-1)!-n!]/(n-1)!=
n![(n+1)(n-1)!-1]/(n-1)!=
n!(n-1)![(n+1) -1/(n-1)!]/(n-1)!=
n![(n+1) -1/(n-1)!] = n![(n+1)(n-1)n! - 1]/(n-1)n!

d) (n+1)!(n-1)!/(n!)² =
n!(n+1)(n-1)!/(n!)² = (n+1)(n-1)!/n! = (n+1)(n-1)n!/n! = (n²-1)